2022-RA-1696-ESGO Impact of ERAS implementation for vulvar cancer surgery. (20th October 2022) - Warkus, Thomas; Feng-Emond, Audrey; Serra Pina, Annick Orvoine; Hillmann, Elise de Castro; Samouëlian, Vanessa
Abstract : Introduction/Background: Surgical literature and information on vulvar cancer is restricted. Centre hospitalier de l'Université de Montréal (CHUM) has a high volume of vulvar cancer patients. Gynaecological Enhanced Recovery after Surgery(ERAS) guidelines was implemented in 2017. This study compares CHUM's practices to available ERAS guidelines, evaluates ERAS compliance and the impact of its implementation on vulvar cancer outcome. Methodology: A retrospective cohort study was conducted at CHUM and included vulvar cancer patients operated in 2015 (pre-ERAS implementation) and 2019–2020 (post-ERAS implementation). Same day discharge and non-elective patients were excluded. Vulvar surgery and gynaecologic oncology ERAS guidelines were compared to CHUM's practices by comparing protocol items. ERAS impact was measured by comparing pre-post implementation cohorts: length of stay (LOS), rates of complications, readmissions, and survival outcomes. Statistical significance was 0.05. Results: 78.9% of CHUM's practices correspond with ERAS vulvar surgery guidelines ( table 1 ). 113 patients were analysed: 51(45.1%) pre-ERAS and 62(54.9%) post-ERAS. Histological types were 69, 9% squamous-cell carcinoma, 5.3% adenocarcinoma, 4.4% melanoma, 5.3% squamous-cell carcinoma with other components, 9.7% persistent VIN-III, and 5.3% Paget's disease. 73.5% of patients had primary treatment and 23% had an adjuvant treatment. Compliance increased from 50.84% pre-ERAS to 56.89% post-ERAS (p=0.523). Post-operative LOS significantly decreased from 7 to 3 nights (p=0.004). No serious complication occurred during hospitalisation, only one serious complication in post-ERAS cohort occurred after hospitalisation. Readmissions decreased from 11.8% to 4.8% (p=0.173). Survival analysis was conducted on stages I-II squamous-cell carcinoma; no significant difference was found between pre-post implementation on overall survival (p=0.277) and disease-free survival (p=0.671). Conclusion: Although CHUM's practices correspond to 78.9% of the ERAS vulvar surgery guidelines, our compliance remains below 60% and did not significantly increase after ERAS implementation. This might be due to a lack of documentation in patients' record. The main impact of ERAS implementation was the LOS significant decrease.